Distribution, Behavior, and Sources of Polycyclic Aromatic Hydrocarbon in the Water Column, Sediments and Biota of the Rufiji Estuary, Tanzania - Shilla, Dativa J.; Routh, Joyanto (Frontiers in Earth Science, 2018)
To establish the environmental status of Rufiji coastal waters in Tanzania, it is necessary to document the different contaminants as major entry points into the lower estuarine areas. Because there is no data on polycyclic aromatic hydrocarbon (PAH) contamination in this estuarine delta, the current study measured the concentrations of 19 PAHs in suspended particulate matter (SPM), surface sediments and marine organisms that are part of a telescoping food chain (gastropod Terebralia sp., clams Crassostrea cucullata, crabs Uca sp., panaeid shrimps Panaeus monodon, teleost Hilsa kelee, Trichiurus lepturus, and Arius thalassinus). Total PAH concentrations in SPM were low to moderate (18.7–223 ng/g) and varied between the sites; phenanthrene and chrysene were the dominant PAHs (2.40–47.2 and 4.20–28.1 ng/g, respectively). Significant variation between the sites indicates the inﬂuence of fuel spills and contribution from terrestrial sources resulting from different land use practices, such as agriculture, fishing, and harvesting firewood, charcoal, and mangroves poles. PAH concentrations in surface sediments were higher (127–376 ng/g) than SPM samples, and high molecular weight PAHs were the dominant fraction. Animal tissues indicated low PAH levels (9.20–158 ng/g). Only low molecular weight PAHs were dominant in the muscle tissues of pelagic and filter feeders (C. cucullata, P. monodon, and H. kelee). Bioaccumulation factor (BAF) ranged between 0.20 and 69.5 and it suggests 1) PAH accumulation in the marine organisms has so far been limited, and 2) distribution of PAHs in the Rufiji estuary poses limited risks.